2022
DOI: 10.1002/acr.24587
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Rheumatoid Arthritis, Multimorbidity, and Adverse Health‐Related Outcomes: A Systematic Review

Abstract: Objective Multimorbidity (the coexistence of two or more long‐term conditions) is highly prevalent in people who have rheumatoid arthritis (RA). The present work systematically reviewed the literature to determine the effect of multimorbidity on all‐cause mortality, functional status, and quality of life in RA. Methods Six electronic databases were searched: CINAHL, The Cochrane Library, Embase, Medline, PsycINFO, and Scopus. Full‐text longitudinal observational studies in English were selected. Quality apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
(180 reference statements)
1
12
0
Order By: Relevance
“…a systematic review has demonstrated an association between rheumatoid arthritis, multimorbidity, and increased all-cause mortality. 26 a registry-based cohort study from Denmark has similarly identified that compared to patients with oa, patients with rheumatoid arthritis had a greater risk of death within one year of primary hip and Ka. 27 these authors identified that glucocorticoid exposure and active inflammation significantly increased the risk of PJI and mortality in these patients.…”
Section: Revised Vs Intactmentioning
confidence: 99%
“…a systematic review has demonstrated an association between rheumatoid arthritis, multimorbidity, and increased all-cause mortality. 26 a registry-based cohort study from Denmark has similarly identified that compared to patients with oa, patients with rheumatoid arthritis had a greater risk of death within one year of primary hip and Ka. 27 these authors identified that glucocorticoid exposure and active inflammation significantly increased the risk of PJI and mortality in these patients.…”
Section: Revised Vs Intactmentioning
confidence: 99%
“…Multimorbidity is common in patients with rheumatoid arthritis (RA), and it is associated with increased mortality, poorer quality of life and increased healthcare utilisation 1 2. The concept of multimorbidity, which is patient-centric instead of focused on the index disease, is important for patients with RA due to the systemic nature of the disease 3.…”
Section: Introductionmentioning
confidence: 99%
“…This finding held true even in subgroup analysis by age category, where having RA “aged” the youngest enrollees by 2–3 decades in terms of multimorbidity burden. This higher multimorbidity in all enrollees with RA is concerning, as multimorbidity is associated with worse functioning (12,25), reduced quality of life (12,26), and higher mortality (12,25). Although previous studies have also shown a >2‐fold increased risk of multimorbidity in RA patients (10), the relative lack of difference in multimorbidity burden by race and ethnicity was a novel finding of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity, defined as presence of ≥2 comorbidities (10), also has a strong impact on RA outcomes. For example, multimorbidity lowers the likelihood of RA remission, reduces functional status, reduces quality of life, and increases mortality, compared to individuals without RA (11,12). In fact, multimorbidity accounts for most of the excess mortality in RA after RA diagnosis (13).…”
Section: Introductionmentioning
confidence: 99%